Analisis Determinasi Belanja Daerah (Studi Kasus Kota/Kabupaten Jawa Tengah Periode 2018 -2019) - Wahyuningsih, Riski; Hutajulu, Dinar Melani (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2022)
The reason for the investigation was to dissect the impact of regional original revenue, general allocation fund, special allocation fund, regional expenditure on provincial uses in urban areas/locale in Central Java. Utilizing optional information acquired from the Central Java Statistics Agency and related office writing. The insightful technique for this examination is the different relapse experimental model and old style supposition testing through the Eviews 10 program. The consequences of the proposed theory test, two free factors significantly affect territorial spending, and one autonomous variable has no critical impact on provincial spending. Local unique pay and uncommon exchange reserves have a positive and huge impact on local spending, while general exchange reserves have a negative and inconsequential impact on provincial spending. It very well may be seen that at the same time the three free factors utilized affect provincial spending in the city/regency of the region of Central Java.